2009
DOI: 10.2174/156802609789869664
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Treatment in Ischemic Stroke Treatment

Abstract: Antiplatelets represent a diverse group of agents that share the ability to reduce platelet activity through a variety of mechanisms. Antithrombotic agents are effective in the secondary prevention of ischemic strokes. Most strokes are caused by a sudden blockage of an artery in the brain (called an ischaemic stroke) that is usually due to a blood clot. Immediate treatment with antiplatelet drugs such as aspirin may prevent new clots from forming and hence improve recovery after stroke. Several studies have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Recurrence results in poor prognosis in patients with ischemic stroke, and antiplatelet therapy has been recommended for the secondary prevention of stroke in patients with a history of noncardioembolic stroke or TIA to reduce nonfatal MI, nonfatal stroke, or vascular death. 39,40 In the present study, we also found that dual antiplatelet therapy was superior to aspirin alone for the prevention of END and RIS. Dual antiplatelet therapy, compared with aspirin alone, was not associated with an increased incidence of hemorrhage.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Recurrence results in poor prognosis in patients with ischemic stroke, and antiplatelet therapy has been recommended for the secondary prevention of stroke in patients with a history of noncardioembolic stroke or TIA to reduce nonfatal MI, nonfatal stroke, or vascular death. 39,40 In the present study, we also found that dual antiplatelet therapy was superior to aspirin alone for the prevention of END and RIS. Dual antiplatelet therapy, compared with aspirin alone, was not associated with an increased incidence of hemorrhage.…”
Section: Discussionsupporting
confidence: 73%
“…The role of antiplatelet drugs may be different in each subtype of stroke. 40 Several studies have reported that combination therapy with clopidogrel and aspirin is more effective than aspirin alone in reducing microembolic signals and recurrent stroke in patients with predominantly intracranial symptomatic stenosis. 20,21 However, among patients with recent lacunar strokes, the addition of clopidogrel to aspirin therapy did not significantly reduce the risk of recurrent stroke but did significantly increase the risk of bleeding and death.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, ASA administration has been shown to reduce stroke and myocardial infarction severity. 30,31 However, individuals that experience recurrent thrombotic events while undergoing aspirin therapy may be classified as "aspirin resistant". ASA resistance is thought to be caused by the inability of ASA to exert inhibitory effects on platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] However, there is little evidence suggesting that non-steroidal anti-inflammatory drugs (NSAIDs) are effective in preventing cognitive decline following stroke.…”
Section: Current and Future Developments In Thementioning
confidence: 99%